Médiation en didactique des langues vivantes. - Sophie Dufossé Sournin (Recherches en didactique des langues et des cultures)
This article focuses on the development of a pedagogical tool integrated into the training of future secondary education teachers of English in XXX Superior School of Education. The aim is to provide class works that have already been carried out in classes by in-service teachers to pre-service students preparing the oral tests included into their final competitive exam. The device is to be used online (LMS) after having been digitized by a School student in Education Engineering. This experiment explores the teacher/trainee/student relationship. Thus it questions the university teacher face-to-face lectures compared to a collaborative pre-service student training.